Adsorption and desorption properties of Li+ on PVC-H1.6Mn1.6O4 lithium ion-sieve membrane - Zhu, Guiru; Wang, Pan; Qi, Pengfei; Gao, Congjie (Chemical engineering journal (Lausanne, Switzerland : 1996), 2014)
[Display omitted] •PVC-Li1.6Mn1.6O4 precursor membranes were prepared by the solvent exchange method.•The lithium ion-sieve membrane has high selectivity for Li+ with coexisting ions.•It exhibits high stability after eight repeated adsorption–desorption cycles.•The thickness of membrane effects on adsorption capacity and mechanical strength. A series of PVC-Li1.6Mn1.6O4 precursor membranes were prepared by the solvent exchange method using spinel-type lithium manganese oxide powder (Li1.6Mn1.6O4) as the precursor, poly(vinyl chloride) (PVC) as the binder, and N,N-dimethyl acetamide (DMAc) as solvent. The Li+ of the precursor membrane was extracted by treated with HCl solution to obtain PVC-H1.6Mn1.6O4 lithium ion-sieve membrane adsorbent. The preparation conditions were investigated by changing the concentration of PVC and Li1.6Mn1.6O4, and the thickness of liquid film. The structure, morphology and adsorption properties of PVC-H1.6Mn1.6O4 lithium ion-sieve membrane were carried out by scanning electron microscope and atomic absorption spectrophotometer. The adsorption capacity depended on the preparation conditions. The membrane prepared with concentration of 10wt% PVC and 15wt% Li1.6Mn1.6O4 in DMAc and liquid film thickness of 0.30mm is optimum for the adsorption of Li+ from aqueous solution. The thickness of membrane prepared under above conditions is about 0.1mm. Repeated adsorption–desorption test indicates that the PVC-H1.6Mn1.6O4 lithium ion-sieve membrane can be effectively regenerated with HCl solution and reused for Li+ adsorption without significant loss in the adsorption capacity. Li+ adsorption experiments confirm that the PVC-H1.6Mn1.6O4 lithium ion-sieve membrane possesses high selectivity for Li+ in the presence of Na+, K+, Ca2+ and Mg2+. According to the coefficients, the isothermal data correlated with the Langmuir model better than the Freundlich model, and the adsorption process follows a pseudo-second-order kinetic model.